Pengaruh Literasi Keuangan, Financial Capability, dan Financial Behavior terhadap Kinerja Keuangan UMKM Kota Bima - Huda, Nurul; Pratiwi, Aliah; Koerniawan, Iwan (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2026)
This study examines the effects of financial literacy, financial capability, and financial behavior on the financial performance of micro, small, and medium enterprises (MSMEs) in Bima City. A quantitative explanatory design was applied to 100 MSME owners selected through purposive sampling, requiring the business to have operated for at least two years. Data were analyzed using partial least squares structural equation modeling (PLS-SEM) in SmartPLS 4. The measurement model met internal consistency and convergent validity criteria, with composite reliability values of 0.871–0.920 and average variance extracted values of 0.583–0.628. The structural model explained 76.4% of the variance in financial performance. Financial behavior had the strongest positive effect on financial performance (β = 0.493; t = 5.183; p < 0.001), followed by financial literacy (β = 0.315; t = 3.485; p < 0.001) and financial capability (β = 0.174; t = 2.127; p = 0.033). These findings indicate that financial knowledge and capability improve MSME financial performance most effectively when translated into disciplined financial practices. The study recommends integrated financial education, bookkeeping assistance, cash-flow planning, and continuous mentoring for MSME owners.